A modular and synthetic biosynthesis platform for de novo production of diverse halogenated tryptophan-derived molecules - Kevin B. Reed; Sierra M. Brooks; Jordan Wells; Kristin J. Blake; Minye Zhao; Kira Placido; Simon d’Oelsnitz; Adit Trivedi; Shruti Gadhiyar; Hal S. Alper (Nature Communications, 2024)
Abstract Halogen-containing molecules are ubiquitous in modern society and present unique chemical possibilities. As a whole, de novo fermentation and synthetic pathway construction for these molecules remain relatively underexplored and could unlock molecules with exciting new applications in industries ranging from textiles to agrochemicals to pharmaceuticals. Here, we report a mix-and-match co-culture platform to de novo generate a large array of halogenated tryptophan derivatives in Escherichia coli from glucose. First, we engineer E. coli to produce between 300 and 700 mg/L of six different halogenated tryptophan precursors. Second, we harness the native promiscuity of multiple downstream enzymes to access unexplored regions of metabolism. Finally, through modular co-culture fermentations, we demonstrate a plug-and-play bioproduction platform, culminating in the generation of 26 distinct halogenated molecules produced de novo including precursors to prodrugs 4-chloro- and 4-bromo-kynurenine and new-to-nature halogenated beta carbolines.